Dysregulated microRNAs in colorectal carcinogenesis: New insight to cell survival and apoptosis regulation. Issue 12 (26th May 2019) - Anvarnia, Alireza; Mohaddes‐Gharamaleki, Farzad; Asadi, Milad; Akbari, Morteza; Yousefi, Bahman; Shanehbandi, Dariush
Abstract: Colorectal cancer (CRC) is the third most common cancer and a leading cause of cancer‐related death worldwide. About 1.8 million new cases were reported in 2018. Accordingly, there is an urgent need for development of effective strategies to lower the mortality and morbidity originated from this malignancy. MicroRNAs (miRNAs) play key roles in several cellular events. They have attracted a great deal of attention in the etiology of a variety of disorders including cancer and might be considered as disease biomarkers or treatment targets. Initiation and development of CRC is a multistep process that is caused by loss of function (LOF) or gain of function (GOF) in genes of different signaling pathways. Particular miRNAs conduct oncogenic impacts by suppressing their target transcripts and simulate the effects of LOF or GOF, whereas there may be no sign of common genetic or epigenetic modifications. On the contrary, some miRNAs serve as tumor suppressor and help to maintain normal functioning and cellular homeostasis. Hence, highlighting the function of each individual miRNA in CRC tumorigenesis could assign it as a therapeutic target or molecular marker for further investigations. In the present review, we have tried to compile the latest information regarding the dysregulated miRNAs in CRC and their function in different disease stages and signaling pathways involved. Abstract : 1. Differentially expressed microRNAs (miRNAs) could serve as diagnostic, prognostic, and predictive biomarkers of colorectal cancer. 2. Engineered expression of miRNAs could be an effective therapeutic strategy in the treatment of colorectal cancer.